A profile of isometric cervical strength in elite professional male rugby players - Liston, M.; Dahly, D.; McLoughlin, R.; Falvey, É.; Fuller, C.; Falla, D.; van Dyk, N. (British Journal of Sports Medicine, 2021)
Background Rugby Union, a popular full-contact sport played throughout the world, has one of the highest rates of concussion of all full-contact sports. Concussion is the most commonly reported injury in rugby matches with 17% of professional players sustaining a concussion in a given season. Cervical muscle strengthening is often included in concussion rehabilitation and/or prevention protocols however the cervical strength profiles of elite rugby players are currently unknown.